The Effect of Administration of Rutin on Plasma Levels of Estrogen, Prolactin, Growth Hormone and Gene Expression of Their Receptors in Mammary Glands in Ovariectomized Rats - Xu-dong GUO; Qi-yu DIAO; Yue-ying WANG; Yan TU; Kai-dong DENG; Xin-jian WANG; Tong FU; Gui-long YAN (Journal of Integrative Agriculture, 2012)
The development of mammary glands, endocrine hormone concentrations and the gene expression of related receptors were measured in ovariectomized virgin rats after adminstration of an estrogen-like plant extract, rutin. Thirty-two ovariectomized virgin Wistar rats were randomly assigned to 4 treatments with 8 animals each: gastric infusion of 2 mL normal saline per unovariectomized rat per day (Sham), gastric infusion of 2 mL normal saline per ovariectomized rat per day (Ova), gastric infusion of 60 mg rutin kg−1 body weight (BW) per ovariectomized rat per day (Ova+Rut), or intramuscular injection of 60 μg estradiol kg−1 BW per ovariectomized rat weekly (Ova+Est). Samples of blood and mammary glands were harvested to determine the levels of estrogen (E2), prolactin (PRL) and growth hormone (GH), and the gene expression of estrogen receptors (ER), prolactin receptors (PRLR) and growth hormone receptors (GHR) with radioimmunoassy (RIA) and RT-PCR technology, respectively. The E2 concentration in plasma and gland tissues from the rats of Ovx+Rut or Ovx+Est was higher than that of Ovx (P<0.05), but the plasma E2 concentration from the rats of Ovx+Rut was lower than that of Sham (P<0.05). The order of the PRL concentration in plasma and gland tissues was Ovx<Ovx+Rut<Ovx+Est <Sham, and the difference in each treatment (P<0.05). The plasma GH concentration was lower in Ovx than in Ovx+Rut or Ovx+Est, and lower in Ovx+Rut than in Sham (P<0.05). The GH concentration in gland tissues was lower in Ovx than in Ovx+Rut or Ovx+Est (P<0.05), and lower in Ovx+Rut than in Sham (P<0.05). The gene expression of ER in gland tissues was increased in an order as Ovx<Ovx+Rut<Ovx+Est<Sham (P<0.05), and PRLR, GHR showed the same trend. In conclusion, adminstration of rutin increased the E2 concentration in plasma and mammary glands, promoted pituitary PRL and GH release, up-regulated the gene expression of ER, PRLR and GHR, and stimulated mammary development in ovariectomized virgin rats.